Natural-Based Cosmetics: Trends, Challenges, and Scientific Innovations - Herayati, Herayati; Elianasari, Elianasari (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM), Institut Teknologi Sumatera, Lampung Selatan, Lampung, Indonesia, 2024)
The increasing demand for natural-based cosmetics has reshaped the beauty industry, driven by consumers seeking sustainable, eco-friendly, and ethically sourced products. This review explores the current trends, formulation challenges, and scientific innovations in the development of natural-based cosmetics. Key natural ingredients, such as plant extracts, oils, and waxes, are discussed in terms of their benefits, limitations, and formulation complexities. The article also addresses significant hurdles, including stability issues, the need for natural preservation systems, and consumer expectations for product efficacy and sensory experience. Advances in green chemistry, biotechnology, and encapsulation technologies are highlighted as critical drivers for overcoming these challenges. Innovations such as plant stem cells, microbial fermentation, and nanoemulsions have enhanced the performance and stability of natural actives. Looking ahead, the future of natural-based cosmetics lies in further integration of green biotechnologies to create more effective and sustainable bioactive ingredients. By embracing these innovations, the beauty industry is poised to meet consumer demands for high-performance products that are not only natural but also sustainable and ethically transparent.